RICE PARBOILING WASTEWATER IN THE MAXIMIZATION OF CAROTENOIDS BIOPRODUCTION BY Phaffia rhodozyma - Danielle Alves da Silva Rios; Thais de Matos de Borba; Susana Juliano Kalil; Janaína Fernandes de Medeiros Burkert (Ciência e Agrotecnologia, 2015)
The interest in carotenoid production from natural sources has increased based in their possible use as dyes and their powerful biological antioxidant capacity. This study evaluated the use of rice parboiling wastewater (RPW) as an alternative substrate for the bioproduction of carotenoids using the yeast Phaffia rhodozyma and found it to be promising as the only source of nutrients, reaching a concentration of 0.6 μg mL-1 (259.1 μg g-1) in 48 h. To increase the potential use of this industrial effluent, a study of supplementation was carried out to enhance the production of carotenoids using the methodology of experimental design (a 2IV 6-2 fractional factorial design sequenced by a 24 central composite design). The conditions for maximizing the production of carotenoids were (g L-1) malt extract (16.25), peptone (8.75), sucrose (15) and rice parboiling wastewater (87.5), with a pH of 5 at 25 °C and 150 rpm for 144 h, which produced a concentration 5.3 μg mL-1 (628.8 μg g-1).